Isolated liver tuberculosis (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Isolated liver tuberculosis is still considered a rare condition and its atypical clinical presentation challenges the clinical acumen of the treating physician. There is difficulty in reaching the correct preoperative diagnosis of nodular hepatic tuberculosis that presents as a space-occupying lesion. It is usually unsuspected and confused with primary or metastatic carcinoma of the liver. In this report, we describe a rare case of isolated liver tuberculosis.